2016
DOI: 10.1002/anie.201607754
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Telechelic Polyethylene by Selective Insertion Polymerization

Abstract: A single-step route to telechelic polyethylene (PE) is enabled by selective insertion polymerization. Pd II -catalyzed copolymerization of ethylene and 2-vinylfuran (VF) generates a,w-di-furan telechelic polyethylene. Orthogonally reactive exclusively in-chain anhydride groups are formed by terpolymerization with carbic anhydride. Combined experimental and theoretical DFT studies reveal the key for this direct approach to telechelics to be a match of the comonomers different electronics and bulk. Identified es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…They copolymerize ethylene with as urprisingly wide variety of polar monomers (both group A and group B monomers). [57] Chen and co-workers showed that the polymerization properties of phosphinesulfonate palladium and nickel catalysts can be improved by the introduction of ap olyethylene glycol unit. [53] However,t heir low activities and low copolymer molecular weights are some of the main limitations.Recently, Nozaki and co-workers showed that the copolymer molecular weights can be significantly increased using am enthyl substituent.…”
Section: Developments Using the Brookhart And Drent Catalystsmentioning
confidence: 99%
“…They copolymerize ethylene with as urprisingly wide variety of polar monomers (both group A and group B monomers). [57] Chen and co-workers showed that the polymerization properties of phosphinesulfonate palladium and nickel catalysts can be improved by the introduction of ap olyethylene glycol unit. [53] However,t heir low activities and low copolymer molecular weights are some of the main limitations.Recently, Nozaki and co-workers showed that the copolymer molecular weights can be significantly increased using am enthyl substituent.…”
Section: Developments Using the Brookhart And Drent Catalystsmentioning
confidence: 99%
“…Recently, several palladium‐ and nickel‐based catalysts have been reported with these capabilities . For example, phosphine sulfonate and related palladium catalysts have been extensively studied and can copolymerize ethylene with various polar comonomers …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] For example,phosphine sulfonate and related palladium catalysts have been extensively studied and can copolymerize ethylene with various polar comonomers. [17][18][19][20][21][22][23] In contrast to the numerous studies focused on catalyst development, fewer studies concerning the material proper-ties of polar-functionalized polyolefins,s uch as density, viscosity,s urface properties,d yeing properties,a nd mechanical properties,have been reported. [24][25][26][27][28][29] Moreover,the polar polyolefins in these studies were limited to thermoplastic-type materials.I n2 014, Mecking and co-workers reported the synthesis of polyolefins bearing siloxanes/glycidyl/anhydride groups via phosphine-sulfonate palladium-catalyzed copolymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to simple ligand modifications and developments, some alternative strategies have recently emerged. For example, Chen et al recently reported redox‐controlled olefin polymerization and copolymerization (Scheme , II ) , . In the phosphine–sulfonate Pd II catalysts, the installed ferrocene unit could be reversibly oxidized and reduced, leading to different reactivity towards olefin monomers.…”
Section: Introductionmentioning
confidence: 99%